A pyridine-doped modified graphite phase carbon nitride photocatalyst, preparation method and application thereof
By introducing pyridine-2-formaldehyde into graphite phase carbon nitride, forming a conjugated structure and increasing specific surface area, the problem of low efficiency in the photocatalytic hydrogen peroxide process is solved, yield and efficiency are significantly improved, and green synthesis is achieved The goal of hydrogen oxide.
Patent Information
- Application Number
- CN202211461379.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-11-17
AI Technical Summary
In the existing photocatalytic methods, graphite phase carbon nitride (g-C3N4) has problems such as low light energy utilization, high carrier recombination probability and small specific surface area during the photocatalytic hydrogen peroxide process, which limits its catalytic efficiency. and application.
By introducing pyridine-2-formaldehyde into graphite phase carbon nitride, the Schiff base reaction is used to generate a conjugated structure, narrow the band gap, increase the probability of photogenerated carrier generation, and improve the specific surface area through pore-making strategies, thereby increasing the Hydrogen oxide yield.
Under neutral conditions, the hydrogen peroxide yield of pyridine-doped modified graphite phase carbon nitride photocatalysts was significantly improved, reaching 2.04 times that of undoped, and reaching 637 μmol/L under acidic conditions, showing a higher Photocatalytic efficiency and stability.
Smart Images

Figure CN115845896B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic materials, and in particular relates to a pyridine-doped modified graphite phase carbon nitride photocatalyst, a preparation method and application thereof in green synthesis of hydrogen peroxide. Background Art
[0002] Hydrogen peroxide is a commonly used oxidant in chemistry and chemical industry, and its reduction product is water. Its green and environmentally friendly characteristics make it widely used in many fields such as disinfection, bleaching, and chemical synthesis. At present, hydrogen peroxide is mainly synthesized by the anthraquinone method using hydrogen and oxygen as raw materials in industry. This method has problems such as high energy consumption, many by-products (such as 2-ethyltetrahydroanthraquinone and octahydroanthraquinone), high price (precious metal palladium as a catalyst), and difficulty in product separation. How to efficiently synthesize hydrogen peroxide has attracted much attention. Among many methods, photocatalytic methods are widely favored by scientific researchers. On the one hand, this is because sunlight is an inexhaustible and clean energy source; on the other hand, oxygen can directly undergo redox reactions with photogenerated electrons on the surface of the catalyst to generate hydrogen peroxide, and there is no hydrogen and oxygen mixing process. The conditions are mild and there is no risk of explosion, so the production is relatively safe.
[0003] Since Professor Akira Fujishima first used titanium dioxide as a photocatalyst to produce hydrogen by photolysis of water in the 1970s, research on semiconductor photocatalysts has continued to attract people's attention. 2 Graphitic carbon nitride (g-C3N4) based on the conjugated ring structure formed by hybridization is a typical polymer semiconductor and has been widely used in the field of photocatalysis in recent years. The electron cloud of g-C3N4 is highly delocalized, with a bandgap of about 2.7 eV. It absorbs in the visible light band, but the wide bandgap leads to low utilization of light energy. In addition, the π-conjugated polymerization structure inside g-C3N4 and the π-π stacking conjugation between layers lead to a high probability of carrier recombination; at the same time, its small specific surface area also limits its application. At present, the band gap of g-C3N4 can be reduced and the carrier separation efficiency can be increased through morphology control, element doping, surface modification, heterojunction construction, copolymerization and other methods, thereby effectively improving the catalytic efficiency. Summary of the invention
[0004] The purpose of the present invention is to provide a pyridine-doped modified graphite phase carbon nitride photocatalyst, a preparation method and its application in green synthesis of hydrogen peroxide. The present invention is characterized in that hydrogen peroxide is generated under neutral conditions, which embodies the concept of green chemistry.
[0005] The present invention adopts Schiff base reaction to make the aldehyde group in pyridine-2-formaldehyde and the amino group in g-C3N4 generate carbon-nitrogen double bond, thereby generating a conjugated structure between the pyridine ring and the triazine ring of g-C3N4, reducing the band gap and increasing the probability of generating photogenerated carriers. At the same time, the multi-electron delocalization system of the pyridine ring is used to form a directional electric field in the molecule, inducing the separation of photogenerated electrons and holes, and improving the utilization efficiency of solar energy; the specific surface area is increased by the pore-forming strategy, so that more oxygen can be adsorbed, thereby increasing the yield of hydrogen peroxide. Under acidic conditions of pH=3, irradiated with a 300W xenon lamp with a 420nm filter for 2h, the hydrogen peroxide yield can reach 637μmol / L, which is 2.04 times the hydrogen peroxide yield when pyridine-2-formaldehyde is not added; under neutral conditions without adding acid, the hydrogen peroxide yield can reach 363μmol / L, which is 2.6 times the hydrogen peroxide yield when pyridine-2-formaldehyde is not added.
[0006] The preparation method of a pyridine-doped modified graphite phase carbon nitride photocatalyst of the present invention comprises the following steps:
[0007] (1) adding melamine and cyanuric acid to ethanol, then adding pyridine-2-carboxaldehyde, and stirring and reacting for a period of time under heating in a water bath;
[0008] (2) heating the reaction solution obtained in step (1) and evaporating it to dryness to obtain a white solid;
[0009] (3) placing the white solid obtained in step (2) in a crucible, wrapping it in tin foil and sealing it, then calcining it for a period of time, and naturally cooling it to obtain a yellowish-brown product, namely the pyridine-2-carboxaldehyde-doped modified graphite phase carbon nitride (g-C3N4) photocatalyst described in the present invention.
[0010] Preferably, in step (1), the mass of melamine is 0.5 to 1 g, the mass of cyanuric acid is 1.01 to 1.02 times the mass of melamine, the mass of ethanol is 15 to 20 mL, and the mass of pyridine-2-carboxaldehyde is 1 to 10 μL;
[0011] Preferably, in step (1), the water bath temperature is 60-70°C;
[0012] Preferably, in step (1), the stirring time is 8 to 20 hours and the stirring speed is 600 to 700 rpm;
[0013] Preferably, in step (2), the heating temperature is 60-70° C.;
[0014] Preferably, in step (3), the calcination atmosphere is air, the calcination temperature is 500-600° C., the calcination time is 3-5 h, and the heating rate during calcination is 2-5° C. / min.
[0015] The present invention uses Schiff base reaction in a non-aqueous solvent to adjust the molecular structure of g-C3N4 so that the triazine ring structure and the pyridine ring structure are conjugated. Due to the conjugation effect, the band gap shrinks and the probability of carrier separation increases, thereby improving the performance of the catalyst and achieving efficient photocatalytic production of hydrogen peroxide.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] 1. The raw materials used in the present invention are cyanuric acid, melamine and pyridine-2-carboxaldehyde, which have a wide range of sources, low cost, do not contain metal elements, and are safe and non-toxic.
[0018] 2. Compared with the original g-C3N4, the present invention adjusts the band gap of the photocatalyst by doping pyridine-2-carboxaldehyde, thereby significantly improving the photocatalytic performance.
[0019] 3. The present invention uses cyanuric acid, melamine and pyridine-2-carboxaldehyde as raw materials, and synthesizes pyridine-2-carboxaldehyde-doped g-C3N4 by Schiff base reaction and thermal polymerization, and the operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 a is the X-ray diffraction pattern (XRD) of the products of Examples 2 to 6, using a German Bruker D8Advance X-ray diffractometer (Cu Kαradiation, ), the scanning speed is 10° / min. Figure 1 b is Figure 1 a is an enlarged view within the range of 25° to 30°; Figure 1 It can be seen that after pyridine-2-carboxaldehyde doping, the spacing of the product in the (002) crystal plane direction changes, indicating that the introduction of the pyridine ring will cause the molecular layer spacing to change.
[0021] Figure 2 a is the infrared spectra of the product of Example 2, the product of Example 4, and the product of Example 4 after repeating the photocatalytic experiment 5 times (denoted as D3-5); Figure 2 b is Figure 2 a is between 3500 and 3000 cm -1 The enlarged picture of Figure 2 c is Figure 2 a is between 1800 and 1500 cm -1 A magnified image of Figure 2 It can be seen that the product of Example 2 has a peak at 3081 cm -1 and 1681cm -1The overtones of the stretching vibration and out-of-plane bending vibration of CH appear at the 400 nm wavelength, respectively. This absorption can only exist in the pyridine ring, indicating that the pyridine ring has successfully entered the C3N4 skeleton. The infrared spectra of the product of Example 4 and the product of Example 4 after repeating the photocatalytic experiment 5 times have no change, indicating that the structure of the catalyst has not changed during the photocatalytic process.
[0022] Figure 3 a is the UV-visible diffuse reflection absorption spectrum of the products of Examples 1 to 6 (normalized spectrum with the absorbance at λ=350nm as 1). Compared with Example 1, the absorption of all samples doped with pyridine-2-carboxaldehyde in the visible light band is improved. This indicates that doping with pyridine-2-carboxaldehyde will increase the utilization rate of light and have better catalytic activity under visible light irradiation. Figure 3 b is the band gap curves of Examples 1 to 6 calculated by the Kubelka-Munk equation, from which it can be seen that the band gaps of all products are reduced after being doped with pyridine-2-carboxaldehyde.
[0023] Figure 4 1 and 2 are impedance spectra of the products of Example 1, Example 2 and Example 5, from which it can be seen that the circle radius of the impedance curve decreases after adding pyridine-2-carboxaldehyde, indicating that the addition of pyridine-2-carboxaldehyde promotes the separation of carriers.
[0024] Figure 5 a~f are Mott-Schottky curves of Examples 1~6 at 500~1500 Hz respectively. Figure 5 The slopes of all the Mott-Schottky curves are positive, indicating that Examples 1 to 6 are all n-type semiconductors. The relationship between the intercept of the curve on the X-axis and the flat band potential of Examples 1 to 6 is shown in the following formula:
[0025] E fb (vs NHE, pH = 0) = E fb (vs Hg / Hg2Cl2)+0.059*2*pH+E(Hg / Hg2Cl2)
[0026] Where E fb is the flat band potential, which is equal to the conduction band bottom potential (E cb ) is:
[0027] E cb =E fb (vs NHE, pH = 0) -0.3
[0028] Figure 6Schematic diagram of the energy band structure of the products of Examples 1 to 6, from which it can be seen that the band gaps of all samples doped with pyridine-2-carboxaldehyde shrink, among which the band gap of Example 4 shrinks to the highest degree, indicating that after doping with pyridine-2-carboxaldehyde, photogenerated electrons are more likely to enter the conduction band and the probability of carrier separation is increased.
[0029] Figure 7 The performance spectrum of the products of Examples 1 to 6 in the photocatalytic production of hydrogen peroxide under acidic conditions of pH = 3. The horizontal axis is the illumination time, and the vertical axis is the yield of hydrogen peroxide. It can be seen from the figure that under continuous 2h of visible light irradiation, compared with Example 1, the yield of hydrogen peroxide produced by all photocatalysts doped with pyridine-2-carboxaldehyde is improved, among which Example 4 has the highest yield of 636μmol / L.
[0030] Figure 8 The performance spectrum of the products of Examples 2 to 6 in the photocatalytic production of hydrogen peroxide under neutral conditions. The horizontal axis is the illumination time, and the vertical axis is the yield of hydrogen peroxide. It can be seen from the figure that under continuous 2h of visible light irradiation, compared with Example 2, the yield of hydrogen peroxide produced by all photocatalysts doped with pyridine-2-carboxaldehyde is improved, among which Example 5 has the highest yield of 364μmol / L.
[0031] Fig. 9 The cyclic stability test of the product of Example 5 for photocatalytic production of hydrogen peroxide under neutral conditions shows that the performance of the product of Example 5 is maintained at more than 80% after 4 consecutive catalysis and more than 75% after 5 consecutive catalysis, indicating that the structure of g-C3N4 doped with pyridine-2-carboxaldehyde does not change during photocatalysis and has good stability.
[0032] Fig.10 The fluorescence spectra of the products of Examples 2-6 are shown in Table 1. The stronger the fluorescence intensity, the higher the probability of carrier recombination and the lower the photocatalytic activity. It can be seen that the fluorescence intensity of g-C3N4 doped with pyridine-2-carboxaldehyde is less than that of undoped g-C3N4, indicating that after doping, the probability of recombination of photogenerated holes and charges is reduced. This is conducive to improving the activity of the photocatalyst.
[0033] Fig.11 The adsorption-desorption isotherms of the products of Example 1, Example 2 and Example 4 show that the specific surface area of g-C3N4 increases after modification with pyridine-2-carboxaldehyde, which indicates that the modified g-C3N4 can adsorb more oxygen molecules and better utilize light energy.
[0034] Fig.12 is the standard curve prepared by Example 10, from Fig.12 It can be seen that the absorbance (Abs) and hydrogen peroxide concentration (M H2O2(mmol)) is: Abs = -0.014 + 0.61 * (M H2O2 ), correlation coefficient r 2 =0.99847>0.99. Therefore, this fitting curve can be used as the standard curve. DETAILED DESCRIPTION
[0035] Example 1: A method for preparing bulk g-C3N4 (BCN), comprising the following steps:
[0036] (1) Put 20 g of melamine into a mortar and grind it thoroughly.
[0037] (2) The solid was poured into a crucible with a lid, wrapped with tin foil and calcined in a muffle furnace. The calcination procedure was as follows: the temperature was raised to 550°C at a rate of 2°C / min, maintained for 4 hours, and then cooled naturally to obtain 6.14 g of a pale yellow-green bulk phase g-C3N4 (denoted as BCN). The photocatalytic production of hydrogen peroxide under acidic conditions was 312 μmol / L, and the photocatalytic production of hydrogen peroxide under neutral conditions was 195 μmol / L.
[0038] Example 2: A method for preparing undoped pyridine-2-carboxaldehyde g-C3N4 nanotubes (D0), comprising the following steps:
[0039] (1) Add 0.5 g of melamine and 0.51 g of cyanuric acid to 15 mL of ethanol, heat in a water bath at 60°C, and stir to react for 8 h.
[0040] (2) Remove the rotor and place the reaction solution in a 60°C oven until the solution is evaporated to dryness to obtain a white solid.
[0041] (3) The solid was placed in a crucible with a lid, sealed with tin foil, and then placed in a muffle furnace for calcination. The calcination procedure was as follows: the temperature was raised to 550°C at a heating rate of 2°C / min, maintained for 4 hours, and then naturally cooled to obtain 0.3102 g of a light yellow g-C3N4 photocatalyst (denoted as D0).
[0042] X-ray diffraction (XRD) was performed on Example 2 to characterize the Figure 1 , diffraction peaks appear at 13° and 27°. These are the diffraction peaks of g-C3N4 in the (100) crystal plane and (002) crystal plane directions, respectively, indicating that the synthesized product is indeed g-C3N4. The photocatalytic production of hydrogen peroxide by the product obtained in this example under acidic conditions is 332 μmol / L, and the photocatalytic production of hydrogen peroxide under neutral conditions is 136 μmol / L.
[0043] Example 3: A method for preparing 1 μL of pyridine-2-carboxaldehyde-doped g-C3N4 (D1), comprising the following steps:
[0044] (1) Add 0.5 g of melamine and 0.51 g of cyanuric acid to 15 mL of ethanol, add 1 μL of pyridine-2-carboxaldehyde, heat in a water bath at 60°C, and stir to react for 8 h.
[0045] (2) Remove the rotor and place the reaction solution in a 60°C oven until the solution is evaporated to dryness to obtain a white solid.
[0046] (3) The solid was placed in a crucible with a lid, sealed with tin foil, and then placed in a muffle furnace for calcination. The calcination procedure was as follows: the temperature was raised to 550°C at a heating rate of 2°C / min, maintained for 4 hours, and then cooled naturally. 0.3174 g of a light khaki pyridine-2-carboxaldehyde-doped g-C3N4 photocatalyst (denoted as D1) was obtained.
[0047] The product obtained in this example has a similar structure to that of Example 2, and the photocatalytic production of hydrogen peroxide under acidic conditions is 408 μmol / L, and the photocatalytic production of hydrogen peroxide under neutral conditions is 236 μmol / L. Example 4: A method for preparing 3 μL of pyridine-2-carboxaldehyde-doped g-C3N4 (D3), comprising the following steps:
[0048] (1) Add 0.5 g of melamine and 0.51 g of cyanuric acid into 15 mL of ethanol, add 3 μL of pyridine-2-carboxaldehyde, heat in a water bath at 60°C, and stir to react for 8 h.
[0049] (2) Remove the rotor and place the reaction solution in a 60°C oven until the solution is evaporated to dryness to obtain a white solid.
[0050] (3) The solid was placed in a crucible with a lid, sealed with tin foil, and then placed in a muffle furnace for calcination. The calcination procedure was as follows: the temperature was raised to 550°C at a rate of 2°C / min, maintained for 4 hours, and then cooled naturally. 0.312 g of a khaki pyridine-2-carboxaldehyde-doped g-C3N4 photocatalyst (denoted as D3) was obtained.
[0051] The product obtained in this example has a similar structure to that of Example 2, and the photocatalytic production of hydrogen peroxide under acidic conditions is 636 μmol / L, and the photocatalytic production of hydrogen peroxide under neutral conditions is 233 μmol / L. Example 5: A method for preparing 5 μL of pyridine-2-carboxaldehyde-doped g-C3N4 (D5), comprising the following steps:
[0052] (1) Add 0.5 g of melamine and 0.51 g of cyanuric acid into 15 mL of ethanol, add 5 μL of pyridine-2-carboxaldehyde, heat in a water bath at 60°C, and stir to react for 8 h.
[0053] (2) Remove the rotor and place the reaction solution in a 60°C oven until the solution is evaporated to dryness to obtain a white solid.
[0054] (3) The solid was placed in a crucible with a lid, sealed with tin foil, and then placed in a muffle furnace for calcination. The calcination procedure was as follows: the temperature was raised to 550°C at a rate of 2°C / min, maintained for 4 hours, and then cooled naturally. 0.356 g of khaki pyridine-2-carboxaldehyde-doped g-C3N4 photocatalyst (denoted as D5) was obtained.
[0055] The product obtained in this example has a similar structure to that of Example 2, and the photocatalytic production of hydrogen peroxide under acidic conditions is 358 μmol / L, and the photocatalytic production of hydrogen peroxide under neutral conditions is 364 μmol / L. Example 6: A method for preparing 10 μL of pyridine-2-carboxaldehyde doped g-C3N4 (D10), comprising the following steps:
[0056] (1) Add 0.5 g of melamine and 0.51 g of cyanuric acid into 15 mL of ethanol, add 10 μL of pyridine-2-carboxaldehyde, heat in a water bath at 60°C, and stir to react for 8 h.
[0057] (2) Remove the rotor and place the reaction solution in a 60°C oven until the solution is evaporated to dryness to obtain a white solid.
[0058] (3) The solid was placed in a crucible with a lid, sealed with tin foil, and then placed in a muffle furnace for calcination. The calcination procedure was as follows: the temperature was raised to 550°C at a rate of 2°C / min, maintained for 4 hours, and then cooled naturally. 0.3721 g of brown pyridine-2-carboxaldehyde-doped g-C3N4 photocatalyst (denoted as D10) was obtained.
[0059] The product obtained in this example has a similar structure to that of Example 2. The photocatalytic production of hydrogen peroxide under acidic conditions is 349 μmol / L, and the photocatalytic production of hydrogen peroxide under neutral conditions is 185 μmol / L.
[0060] Example 7: Photocatalytic generation of hydrogen peroxide under acidic conditions (pH=3)
[0061] Weigh 50 mg of the catalyst prepared in Examples 1 to 6 respectively, disperse in 50 mL of 10% isopropanol solution (45 mL of deionized water + 5 mL of isopropanol), ultrasonicate for 15 min, add 50 μL of hydrochloric acid to adjust pH=3, and stir in the dark for 1 h to dissolve enough air. The reaction light source is a 300W xenon lamp equipped with a 420nm filter, and the control current is 15A. A constant temperature water circulation system is used to control the reaction temperature, and a 2 mL sample is taken every 20 min, and the total reaction time is 120 min. After centrifugation of all samples, 1 mL of supernatant is taken as the test solution.
[0062] The photocatalytic test of Examples 1 to 6 was carried out under acidic conditions, and the content of hydrogen peroxide in the solution was measured using the method in Example 11. The results are as follows: Figure 7Under acidic conditions, the yield of Example 4 is the highest, reaching 636 μmol / L.
[0063] Example 8: Photocatalytic generation of hydrogen peroxide under neutral conditions (pH=7)
[0064] Weigh 50 mg of the catalyst prepared in Examples 2 to 6 respectively, disperse in 50 mL of 10% isopropanol solution (45 mL of deionized water + 5 mL of isopropanol), ultrasonicate for 15 min, and stir in the dark for 1 h to dissolve enough air. The reaction light source is a 300W xenon lamp equipped with a 420nm filter, and the control current is 15A. A constant temperature water circulation system is used to control the reaction temperature, and a 2 mL sample is taken every 20 min for a total reaction of 120 min. After centrifugation of all samples, 1 mL of supernatant is taken as the test solution.
[0065] The photocatalytic test of Examples 2 to 6 was carried out under neutral conditions, and the content of hydrogen peroxide in the solution was measured by the method in Example 11. The results are as follows: Figure 8 Under neutral conditions, the yield of Example 5 is the highest, reaching 364 μmol / L.
[0066] Example 9: Cyclic stability test
[0067] The solution after each reaction in Example 8 was centrifuged, the solid was collected, washed three times with deionized water, and dried in an oven at 80° C. for 6 h for the next photocatalytic experiment. Five photocatalytic experiments were performed continuously under the same conditions.
[0068] Example 10: Drawing of hydrogen peroxide standard curve
[0069] Take 1.03mL of 30% hydrogen peroxide solution and make up to volume in a 100mL volumetric flask as the mother solution. Take 1, 2, 3, 4, 5, and 6mL of the mother solution respectively and make up to volume in a 100mL volumetric flask to prepare hydrogen peroxide solutions with concentrations of 1, 2, 3, 4, 5, and 6mmol / L.
[0070] Take 1mL of hydrogen peroxide solution with concentrations of 1, 2, 3, 4, 5, and 6mmol / L, add 0.5mL of KI (0.4mol / L) solution, 0.5mL of potassium hydrogen phthalate (0.4mol / L) solution and 3.0mL of ultrapure water respectively, and react for 20min. Use Shimadzu UV-2450 UV-visible spectrophotometer to measure the absorbance of the mixed solution at 352nm, and make a linear fit between the absorbance and the concentration of hydrogen peroxide to obtain the standard curve of hydrogen peroxide and absorbance as shown below: Fig.12 Its correlation coefficient r 2 =0.99847>0.99, indicating that this fitting straight line can be used as a standard curve.
[0071] Example 11: Calculation of the concentration of hydrogen peroxide by colorimetry
[0072] To 1 mL of the hydrogen peroxide solution generated in Example 7, Example 8, and Example 9, 0.5 mL of KI (0.4 mol / L) solution and 0.5 mL of potassium hydrogen phthalate (0.4 mol / L) solution were added respectively, and the reaction was carried out for 20 min. The absorbance of the mixed solution at 352 nm was measured by a UV-visible spectrophotometer, and the corresponding hydrogen peroxide concentration was calculated using the standard curve obtained in Example 10.
Claims
1. A method for preparing a pyridine-doped modified graphite phase carbon nitride photocatalyst for green synthesis of hydrogen peroxide, the steps of which are as follows: (1) Add melamine and cyanuric acid to ethanol, then add pyridine-2-carboxaldehyde, and stir and react for a period of time under heating in a water bath; (2) heating the reaction solution obtained in step (1) and evaporating it to dryness to obtain a white solid; (3) placing the white solid obtained in step (2) in a crucible, wrapping and sealing it, calcining it for a period of time, and naturally cooling it to obtain a yellowish-brown product, namely the pyridine-2-carboxaldehyde-doped modified graphite phase carbon nitride photocatalyst; In step (1), the mass of melamine is 0.5-1 g, the mass of cyanuric acid is 1.01-1.02 times the mass of melamine, the mass of ethanol is 15-20 mL, and the mass of pyridine-2-carboxaldehyde is 1-10 μL; In step (1), the water bath temperature is 60-70°C; In step (2), the heating temperature is 60-70°C; In step (3), the calcination atmosphere is air, the calcination temperature is 500-600°C, the calcination time is 3-5h, and the heating rate during calcination is 2-5°C / min.
2. The method for preparing a pyridine-doped modified graphite phase carbon nitride photocatalyst for green synthesis of hydrogen peroxide as claimed in claim 1, characterized in that: In step (1), the stirring time is 8 to 20 hours and the stirring speed is 600 to 700 rpm.
3. A pyridine-doped modified graphite phase carbon nitride photocatalyst, characterized in that: The method is prepared by any one of claims 1 to 2.
4. Use of a pyridine-doped modified graphite phase carbon nitride photocatalyst as claimed in claim 3 in green synthesis of hydrogen peroxide.
